Legitimacy and civil war onset: Remember the people’s perceptions - Møller, Fenja Søndergaard (Politica, 2016)
This article argues that systematic use of the concept of legitimacy contributes to an understanding of civil war onset. First, legitimacy is defined as the people’s perception of the government as rightfully holding power. Next, a legitimacy index is constructed on the basis of survey data from 49 states. This measurement illustrates that legitimacy captures hitherto neglected motives, which deepen the understanding of civil war in cases such as Nigeria and Ukraine and peace in states like Jordan and Ghana.